2014
DOI: 10.1373/clinchem.2013.216275
|View full text |Cite
|
Sign up to set email alerts
|

Reference Interval Evaluation of High-Sensitivity Troponin T and N-Terminal B-Type Natriuretic Peptide in Vietnam and the US: The North South East West Trial

Abstract: BACKGROUND:Reference intervals of high-sensitivity troponin T (hs-cTnT) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) have been determined from Western populations. No data are available regarding expected values in Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…This value is akin to what we found in 2010 and close to that in our current study (17 ng/L); our 99P decision limit for men and women (18.6 and 12.0 ng/L) was quite similar to that quoted by Apple -20 and 13 ng/L. In one of the largest hs-TnT reference range investigations (n=1157) involving 565 US and 592 Vietnamese volunteers (mean age 41.2 y) screened by questionnaire, a higher Asian male-female hs-TnT cutpoints (25 and 19 ng/L) was found [22]. Giannitsis [13] reported an overall 99P cut-point of 13.5 ng/L for 616 Germans with a mean age of 44±13.4 y while that in men was 14.5 and women 10.0.…”
Section: Reference Populationsupporting
confidence: 82%
“…This value is akin to what we found in 2010 and close to that in our current study (17 ng/L); our 99P decision limit for men and women (18.6 and 12.0 ng/L) was quite similar to that quoted by Apple -20 and 13 ng/L. In one of the largest hs-TnT reference range investigations (n=1157) involving 565 US and 592 Vietnamese volunteers (mean age 41.2 y) screened by questionnaire, a higher Asian male-female hs-TnT cutpoints (25 and 19 ng/L) was found [22]. Giannitsis [13] reported an overall 99P cut-point of 13.5 ng/L for 616 Germans with a mean age of 44±13.4 y while that in men was 14.5 and women 10.0.…”
Section: Reference Populationsupporting
confidence: 82%
“…Regarding the highly sensitive cTnT ECLIA method, variability among the 99th URL values reported in different studies and by manufacturers is very similar (Table 5) [9,12,26,41,124,[126][127][128]. Considering as a whole the clinical studies including a total of 10,078 individuals [9,12,26,47,124,[126][127][128], median (25th-75th percentiles) values of 99th URL results of highly sensitive cTnT ECLIA method are for the overall population 14.6 (13.2-18.0) ng/L, for men 16.0 (15.0-19.5) ng/L, and for women 12.0 (9.6-12.5) ng/L, respectively.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 83%
“…However, the Authors reported that, as expected, in the Vietnamese cohort the median (95% CI) cTnT concentrations in men (4.0 [3.0-5.0] ng/L) were higher than in women (2.5 [2.5-4.09] ng/L). These data [128] suggest that the higher 99th URL value in Vietnamese women was probably due to outlier values not corrected at statistical analysis. Although data reported in Table 4 are significantly heterogeneous (I 2 = 99.93%; p < 0.001), there was also a significant difference between the 99th URL values in men and women for the 99th URL value of cTnT measured using the highly sensitive ECLIA method (4.59 ng/L, SE = 1.5232 ng/L; p = 0.0026).…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 84%
See 1 more Smart Citation
“…Although the prevalence of these false negative results is unknown, it is clear that increased urine hCG␤cf concentrations can be observed during normal pregnancy. The use of such devices poses a risk to patients if treatment is inappropriately administered to pregnant women (4).…”
Section: Authors' Disclosures or Potentialmentioning
confidence: 99%